Torsional Oscillations in Automotive Transmissions: Experimental Analysis and Modelling - Enrico Galvagno; Mauro Velardocchia; Alessandro Vigliani (Shock and Vibration)
The paper investigates the torsional oscillations of an automotive transmission system by means of an experimental test bench used to validate the proposed lumped parameter model. The rig consists of a Dual Clutch Transmission (DCT) and a Manual Transmission (MT) connected through the respective output shafts, while the excitation is provided by two electric motors, which are controlled in speed or torque. The experimental analysis includes the measurement of the external torques, applied by the two electric motors to the mechanical system, and the measurement of the system response in terms of angular speeds at different positions along the transmission line. The frequency response of the system is estimated from the experimental data and compared with the results of a 5-degree-of-freedom lumped parameter model, which proves to be adequate to describe the dynamic behaviour of the system up to a frequency of 200 Hz. The comparison between simulated results and experimental data shows good agreement, so the model can be used to predict the torsional vibrations of the transmission system in the linear field. Moreover, the effects of the nonlinearities associated with the mean value of the excitations are shown. Finally the influence of the selected gear ratio on the experimental frequency response is discussed.